Influence of Multimorbidity on Burden and Appropriateness of Implantable Cardioverter‐Defibrillator Therapies. Issue 7 (20th March 2019) - Hajduk, Alexandra M.; Gurwitz, Jerry H.; Tabada, Grace; Masoudi, Frederick A.; Magid, David J.; Greenlee, Robert T.; Sung, Sue Hee; Cassidy‐Bushrow, Andrea E.; Liu, Taylor I.; Reynolds, Kristi; Smith, David H.; Fiocchi, Frances; et al.
Abstract : OBJECTIVE: To determine whether burden of multiple chronic conditions (MCCs) influences the risk of receiving inappropriate vs appropriate device therapies. DESIGN: Retrospective cohort study. SETTING: Seven US healthcare delivery systems. PARTICIPANTS: Adults with left ventricular systolic dysfunction receiving an implantable cardioverter‐defibrillator (ICD) for primary prevention. MEASUREMENTS: Data on 24 comorbid conditions were captured from electronic health records and categorized into quartiles of comorbidity burden (0‐3, 4‐5, 6‐7 and 8‐16). Incidence of ICD therapies (shock and antitachycardia pacing [ATP] therapies), including appropriateness, was collected for 3 years after implantation. Outcomes included time to first ICD therapy, total ICD therapy burden, and risk of inappropriate vs appropriate ICD therapy. RESULTS: Among 2235 patients (mean age = 69 ± 11 years, 75% men), the median number of comorbidities was 6 (interquartile range = 4‐8), with 98% having at least two comorbidities. During a mean 2.2 years of follow‐up, 18.3% of patients experienced at least one appropriate therapy and 9.9% experienced at least one inappropriate therapy. Higher comorbidity burden was associated with an increased risk of first inappropriate therapy (adjusted hazard ratio [HR] = 1.94 [95% confidence interval CI = 1.14‐3.31] for 4‐5 comorbidities; HR = 2.25 [95% CI = 1.25‐4.05] for 6‐7 comorbidities; and HR = 2.91 [95% CI = 1.54‐5.50] for 8‐16 comorbidities). Participants with 8‐16 comorbidities had a higher total burden of ICD therapy (adjusted relative risk [RR] = 2.12 [95% CI = 1.43‐3.16]), a higher burden of inappropriate therapy (RR = 3.39 [95% CI = 1.67‐6.86]), and a higher risk of receiving inappropriate vs appropriate therapy (RR = 1.74 [95% CI = 1.07‐2.82]). Comorbidity burden was not significantly associated with receipt of appropriate ICD therapies. Patterns were similar when separately examining shock or ATP therapies. CONCLUSIONS: In primary prevention ICD recipients, MCC burden was independently associated with an increased risk of inappropriate but not appropriate device therapies. Comorbidity burden should be considered when engaging patients in shared decision making about ICD implantation.